Toxic in vitro effects of flavoured-air inhalers containing essential oils in differentiated human nasal epithelial cells at air–liquid interface - Alexander N. Larcombe; E. E. Catchpole; P. Hopper; S. Stanley; A. Kicic; K. R. Landwehr (Archives of Toxicology, 2026)
Flavoured-air inhalers containing essential oils are marketed as safe, natural alternatives to smoking and vaping, yet their potential respiratory toxicity remains effectively unexamined. Manufacturers claim safety based on "100% natural" ingredients, despite evidence that essential oil inhalation can cause adverse respiratory effects. Our objective was to assess the in vitro toxicity of six commercially available flavoured-air products on human nasal airway epithelial cells. Differentiated air–liquid interface cultures of primary nasal airway epithelial cells from eight healthy adults were exposed for one hour to air (control) or flavoured air from three devices (Füm, Lio, Cigtrus; two flavours each) generated by drawing air through essential oil-infused cores at a continuous airflow of 1 L/min for one hour into an 1000 mL exposure chamber. Outcomes included transepithelial electrical resistance, cytotoxicity, protein release, cytokine/chemokine profiling and histological assessment. Chemical analysis characterised the chemical composition of device cores and identified 29 compounds across the six products, including the possible carcinogen pulegone and cytotoxic cinnamaldehyde. Five of six flavours significantly reduced transepithelial electrical resistance indicating compromised epithelial barrier integrity. Mediator responses were compartment-specific: apical surfaces showed predominantly pro-inflammatory profiles while basal release was broadly suppressed. Histological analysis revealed reduced cilia coverage, fewer mucus-producing cells, and decreased epithelial thickness across multiple treatments. This study shows that a single one-hour exposure to flavoured-air vapour led to epithelial barrier dysfunction, immune dysregulation, and structural damage in healthy human nasal airway epithelial cells, contradicting manufacturer safety claims. Rigorous toxicological evaluation of these products is urgently needed.

Body Size, Dispersal Potential, Range Size and Habitat Fragmentation Are Linked to Extinction Risk of Freshwater Mussels - Garrett W. Hopper; Sean M. Keogh; Carla L. Atkinson; Traci P. DuBose; Jeffrey D. Lozier; John M. Pfeiffer; Irene Sánchez González (Journal of Biogeography, 2026)
Aim Trait‐based approaches are increasingly recognised as tools for understanding species' vulnerabilities to intensifying global change. For species with complex life histories that involve a parasitic life stage, a combination of traits associated with either the host or parasite could influence extinction risk. Location United States of America. Taxon Freshwater mussels are a highly threatened assemblage of bivalves with an obligate ectoparasitic larval stage requiring a host fish. Adult mussels are sedentary, with long‐distance dispersal dictated by the dispersal ability of the host fish during the parasitic larval life phase. Methods We integrate several open‐source spatial and trait datasets for freshwater mussels and host fishes to test hypotheses about the relationship between species‐level traits such as body size, area of occupancy (AOO), host fish dispersal, habitat fragmentation and mussel extinction risk. Results Imperilled mussels were smaller, had smaller areas of occupancy, used small‐bodied, dispersal‐limited host fishes and had higher densities of large dams in their AOO compared to non‐imperilled mussels. Conclusions Body size, along with AOO and dispersal potential, appears to have cascading effects on imperilment where decreases in these traits potentiate population fragmentation via large dams. Thus, in contrast to many other groups, freshwater mussel body size is inversely related to extinction risk, and small‐bodied mussels should be closely monitored to prevent future extinctions.

Scientists’ warning on the global destruction of rock outcrop ecosystems - Luiza F. A. de Paula; Lucas N. Perillo; Gianluigi Ottaviani; Flávio F. Carmo; Mandar N. Datar; Katherine C. Enebeli‐Ekwutoziam; Bruno Fogliani; Stephen D. Hopper; Aboli Kulkarni; Hans Lambers; Rafael F. Magalhães; Frederico S. Neves; et al. (Conservation Biology, 2026)
Rock outcrops are geological formations that harbor a highly specialized biota adapted to harsh environmental conditions that differ from their surrounding landscapes. They are globally distributed, especially in old, highly weathered landscapes, and can function as habitat islands containing high levels of endemism and distinct evolutionary lineages. Despite their ecoevolutionary importance, rock outcrops remain largely overlooked in global conservation policy, ecosystem typologies, and biodiversity monitoring frameworks. Extractive activities directly remove the geological substrate that underpins these habitats, and climate change intensifies drought, heatwaves, and hydrological instability. Rising global demand for energy‐transition metals required for decarbonization is expected to further accelerate these pressures, particularly in biodiverse regions of the Global South where governance is weaker. Given that rock outcrop ecosystems are ecologically and evolutionarily significant, we devised a policy‐relevant conservation roadmap structured around prevention, mitigation, restoration, and governance issues. Priority actions include recognizing rock outcrops as unique ecosystems in global classifications and ecosystem typologies, integrating them into biodiversity monitoring frameworks, and improving the identification of key biodiversity areas and the International Union for Conservation of Nature (IUCN) Red List of Ecosystems assessments. We call for stronger environmental impact assessments, cumulative‐impact evaluations for mining and quarrying projects, and the designation of mining and quarrying exclusion sites of high irreplaceability. Coordinated international policy, improved ecological data, and meaningful engagement with local and Indigenous communities are essential to safeguard these ancient ecosystems before further, irreversible losses occur.

Depth-dependent azimuthal seismic anisotropy governed by Couette/Poiseuille flow partitioning in the asthenosphere - Zhirui Ray Wang; Clinton P. Conrad; Sergei Lebedev; Giampiero Iaffaldano; John R. Hopper (Earth and Planetary Science Letters, 2025)

Procedural Variation May Contribute to 6-Minute Walk Distance Variability in Real-World Pediatric Pulmonary Arterial Hypertension Study - Cynthia Kleppinger; Dunbar Ivy; Norman Stockbridge; Angela Bates; Stephanie Handler; Usha S. Krishnan; Mary P. Mullen; Delphine Yung; Rachel K. Hopper; Nidhy P. Varghese; Jeff Fineman; Eric D. Austin; et al. (The AAPS Journal, 2025)
The six-minute walk test (6MWT) is a common method to assess submaximal exercise capacity in children and adults with pulmonary arterial hypertension (PAH) and other chronic diseases. There is no guideline specifically for 6MWT in children. In this observational pilot study, we evaluated the impact of procedural variations on the outcome of the 6MWT in the real-world clinical setting at pediatric PAH programs. We collected 6MWT data from 33 children with PAH participating in a multicenter, prospective, non-interventional study. Data range/quantiles and standard deviation (SD) were used to describe distribution of the six-minute walk distance (6MWD) and data variability. Levene’s test was used to test for heterogeneity of variance with the two sites of similar altitude and their age/height/weight-matched Panama Function Class II participants. We analyzed all 33 eligible participants and their qualified first walks at five centers (A-E) with 6MWD ranges of 420–570, 357–683, 418–481, 400–700, 377–549 m, respectively. Site D performed the 6MWT in a busy hallway and allowed parental/caregiver’s cheering, while Site E performed the 6MWT in a secluded area with no parental/caregiver involvement. Mean 6MWD and SD for Sites D and E were 547 (125) and 432 (67.5) meters, respectively (p = 0.03). In conclusion, procedural variations seem to associate with 6MWD data variability. Although interpretation of our results is limited by the small sample size, our findings suggest that standardizing pediatric 6MWT procedures are needed. Graphical Abstract

Habitat engineering effects of freshwater mussels in rivers vary across spatial scales - Traci P. DuBose; Caryn C. Vaughn; Garrett W. Hopper; Keith B. Gido; Thomas B. Parr (Hydrobiologia, 2024)

Daily dynamics of contrasting spring algal blooms in Santa Monica Bay (central Southern California Bight) - Gerid A. Ollison; Sarah K. Hu; Julie V. Hopper; Brittany P. Stewart; Jayme Smith; Jennifer L. Beatty; Laura K. Rink; David A. Caron (Environmental Microbiology, 2022)
Protistan algae (phytoplankton) dominate coastal upwelling ecosystems where they form massive blooms that support the world's most important fisheries and constitute an important sink for atmospheric CO 2 . Bloom initiation is well understood, but the biotic and abiotic forces that shape short‐term dynamics in community composition are still poorly characterized. Here, high‐frequency (daily) changes in relative abundance dynamics of the metabolically active protistan community were followed via expressed 18S V4 rRNA genes (RNA) throughout two algal blooms during the spring of 2018 and 2019 in Santa Monica Bay (central Southern California Bight). A diatom bloom formed after wind‐driven, nutrient upwelling events in both years, but different taxa dominated each year. Whereas diatoms bloomed following elevated nutrients and declined after depletion each year, a massive dinoflagellate bloom manifested under relatively low inorganic nitrogen conditions following diatom bloom senescence in 2019 but not 2018. Network analysis revealed associations between diatoms and cercozoan putative parasitic taxa and syndinean parasites during 2019 that may have influenced the demise of the diatoms, and the transition to a dinoflagellate‐dominated bloom.

Genome Sequence Analysis of Two Pseudomonas putida Strains to Identify a 17-Hydroxylase Putatively Involved in Sparteine Degradation - Andrew P. Detheridge; Gareth W. Griffith; David J. Hopper (Current Microbiology, 2018)

Early-onset baldness and the risk of aggressive prostate cancer: findings from a case–control study - Nathan P. Papa; Robert J. MacInnis; Dallas R. English; Damien Bolton; Ian D. Davis; Nathan Lawrentschuk; Jeremy L. Millar; Gianluca Severi; John L. Hopper; Graham G. Giles (Cancer Causes & Control, 2018)

Improved quality of risk-reducing salpingo-oophorectomy in Australasian women at high risk of pelvic serous cancer - Y. C. Lee; M. Bressel; P. Grant; P. Russell; C. Smith; S. Picken; S. Camm; B. E. Kiely; R. L. Milne; S. A. McLachlan; M. Hickey; M. L. Friedlander; et al. (Familial Cancer, 2017)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Risk of colorectal cancer for people with a mutation in both a MUTYH and a DNA mismatch repair gene - Aung Ko Win; Jeanette C. Reece; Daniel D. Buchanan; Mark Clendenning; Joanne P. Young; Sean P. Cleary; Hyeja Kim; Michelle Cotterchio; James G. Dowty; Robert J. MacInnis; Katherine M. Tucker; Ingrid M. Winship; et al. (Familial Cancer, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

High prevalence of mismatch repair deficiency in prostate cancers diagnosed in mismatch repair gene mutation carriers from the colon cancer family registry - Christophe Rosty; Michael D. Walsh; Noralane M. Lindor; Stephen N. Thibodeau; Erin Mundt; Steven Gallinger; Melyssa Aronson; Aaron Pollett; John A. Baron; Sally Pearson; Mark Clendenning; Rhiannon J. Walters; et al. (Familial Cancer, 2014)

Detection of large scale 3′ deletions in the PMS2 gene amongst Colon-CFR participants: have we been missing anything? - Mark Clendenning; Michael D. Walsh; Judith Balmana Gelpi; Stephen N. Thibodeau; Noralane Lindor; John D. Potter; Polly Newcomb; Loic LeMarchand; Robert Haile; Steve Gallinger; John L. Hopper; Mark A. Jenkins; et al. (Familial Cancer, 2013)

Refugia: identifying and understanding safe havens for biodiversity under climate change - Gunnar Keppel; Kimberly P. Van Niel; Grant W. Wardell‐Johnson; Colin J. Yates; Margaret Byrne; Ladislav Mucina; Antonius G. T. Schut; Stephen D. Hopper; Steven E. Franklin (Global Ecology and Biogeography, 2012)
Aim Identifying and protecting refugia is a priority for conservation under projected anthropogenic climate change, because of their demonstrated ability to facilitate the survival of biota under adverse conditions. Refugia are habitats that components of biodiversity retreat to, persist in and can potentially expand from under changing environmental conditions. However, the study and discussion of refugia has often been ad hoc and descriptive in nature. We therefore: (1) provide a habitat‐based concept of refugia, and (2) evaluate methods for the identification of refugia. Location Global. Methods We present a simple conceptual framework for refugia and examine the factors that describe them. We then demonstrate how different disciplines are contributing to our understanding of refugia, and the tools that they provide for identifying and quantifying refugia. Results Current understanding of refugia is largely based on Quaternary phylogeographic studies on organisms in North America and Europe during significant temperature fluctuations. This has resulted in gaps in our understanding of refugia, particularly when attempting to apply current theory to forecast anthropogenic climate change. Refugia are environmental habitats with space and time dimensions that operate on evolutionary time‐scales and have facilitated the survival of biota under changing environmental conditions for millennia. Therefore, they offer the best chances for survival under climate change for many taxa, making their identification important for conservation under anthropogenic climate change. Several methods from various disciplines provide viable options for achieving this goal. Main conclusions The framework developed for refugia allows the identification and description of refugia in any environment. Various methods provide important contributions but each is limited in scope; urging a more integrated approach to identify, define and conserve refugia. Such an approach will facilitate better understanding of refugia and their capacity to act as safe havens under projected anthropogenic climate change.

Adequacy of risk-reducing gynaecologic surgery in BRCA1 or BRCA2 mutation carriers and other women at high risk of pelvic serous cancer - B. E. Kiely; M. L. Friedlander; R. L. Milne; L. Stanhope; P. Russell; M. A. Jenkins; P. Weideman; S. A. McLachlan; P. Grant; J. L. Hopper; K. A. Phillips (Familial Cancer, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Mutation deep within an intron of MSH2 causes Lynch syndrome - Mark Clendenning; Daniel D. Buchanan; Michael D. Walsh; Belinda Nagler; Christophe Rosty; Bryony Thompson; Amanda B. Spurdle; John L. Hopper; Mark A. Jenkins; Joanne P. Young (Familial Cancer, 2011)

Linkage to chromosome 2q32.2-q33.3 in familial serrated neoplasia (Jass syndrome) - Aedan Roberts; Derek Nancarrow; Mark Clendenning; Daniel D. Buchanan; Mark A. Jenkins; David Duggan; Darin Taverna; Diane McKeone; Rhiannon Walters; Michael D. Walsh; Bruce W. Young; Jeremy R. Jass; et al. (Familial Cancer, 2011)

Analyses of cpDNA matK sequence data place Tillaea (Crassulaceae) within Crassula - Mark Eugene Mort; Christopher P. Randle; Priscilla Burgoyne; Gideon Smith; Ernst Jaarsveld; Stephen D. Hopper (Plant Systematics and Evolution, 2009)

Analysis of families with Lynch syndrome complicated by advanced serrated neoplasia: the importance of pathology review and pedigree analysis - Michael D. Walsh; Daniel D. Buchanan; Rhiannon Walters; Aedan Roberts; Sven Arnold; Diane McKeone; Mark Clendenning; Andrew R. Ruszkiewicz; Mark A. Jenkins; John L. Hopper; Jack Goldblatt; Jillian George; et al. (Familial Cancer, 2009)

Isoetes eludens (Isoetaceae), a new endemic species from the Kamiesberg, Northern Cape, South Africa - J. P. Roux; S. D. Hopper; R. J. Smith (Kew Bulletin, 2009)

A Method for Setting the Size of Plant Conservation Target Areas - Mark A. Burgman; Hugh P. Possingham; A. Jasmyn J. Lynch; David A. Keith; Michael A. McCarthy; Stephen D. Hopper; Wendy L. Drury; Jason A. Passioura; Robert J. Devries (Conservation Biology, 2001)
Realistic time frames in which management decisions are made often preclude the completion of the detailed analyses necessary for conservation planning. Under these circumstances, efficient alternatives may assist in approximating the results of more thorough studies that require extensive resources and time. We outline a set of concepts and formulas that may be used in lieu of detailed population viability analyses and habitat modeling exercises to estimate the protected areas required to provide desirable conservation outcomes for a suite of threatened plant species. We used expert judgment of parameters and assessment of a population size that results in a specified quasiextinction risk based on simple dynamic models. The area required to support a population of this size is adjusted to take into account deterministic and stochastic human influences, including small‐scale disturbance, deterministic trends such as habitat loss, and changes in population density through processes such as predation and competition. We set targets for different disturbance regimes and geographic regions. We applied our methods to Banksia cuneata, Boronia keysii, and Parsonsia dorrigoensis, resulting in target areas for conservation of 1102, 733, and 1084 ha, respectively. These results provide guidance on target areas and priorities for conservation strategies.

Monocrotophos-Induced Mass Mortality of Swainson's Hawks in Argentina, 1995–96 - Michael I. Goldstein; T. E. Lacher; B. Woodbridge; M. J. Bechard; S. B. Canavelli; M. E. Zaccagnini; G. P. Cobb; E. J. Scollon; R. Tribolet; M. J. Hopper (Ecotoxicology, 1999)